2004
DOI: 10.1111/j.1472-8206.2004.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and outcomes of pregnancy after chemotherapy in a sample of childbearing aged women

Abstract: The aim of the study was to review the characteristics and outcomes of pregnancies occurring in women of childbearing age after chemotherapy for malignant disease. Between November 1998 and October 1999, a total of 16 patients who were treated for ovary (three), mole (one), vaginal (one), breast (four), Hodgkin's disease (four), lung (one), melanoma (one) and osteosarcoma (one) carcinoma were identified and retrospectively questioned about their fertility status. All the 16 women included in this study receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Valentgas et al [56] found that miscarriages occurred in 24% of 53 breast cancer survivors compared with 18% of control women without breast cancer of similar ages (Table 4) [43,56,58,59]. Other authors reported that cytotoxic drug exposure had no deleterious effects on subsequent pregnancies in terms of miscarriages or congenital malformation [43,[57][58][59][60][61].…”
Section: Pregnancy After Chemotherapymentioning
confidence: 93%
“…Valentgas et al [56] found that miscarriages occurred in 24% of 53 breast cancer survivors compared with 18% of control women without breast cancer of similar ages (Table 4) [43,56,58,59]. Other authors reported that cytotoxic drug exposure had no deleterious effects on subsequent pregnancies in terms of miscarriages or congenital malformation [43,[57][58][59][60][61].…”
Section: Pregnancy After Chemotherapymentioning
confidence: 93%